Adoption process of portable digital nutrient decision-support technologies: perennial experience of Shaanxi's kiwifruit smallholders - Li, Xia; Hadi, Ahmad Hanis Izani Abdul; Tey, Yeong Sheng; Sidique, Shaufique Fahmi; Mohd Nawi, Nolila (Elsevier B.V., 2026)
Digital decision-support tools for nutrient management have offered a promising entry point to precision agriculture, yet little is known about how smallholders engage with these tools over time. This study aimed to identify the decision stages and temporal pathways through which farmers adopted three portable digital nutrient decision-support technologies (PDDSTs) - soil testers, chlorophyll meters, and agro-advisory mobile applications. Using survey data from 675 kiwifruit growers in Shaanxi Province, China, we reconstructed adoption trajectories using Sankey diagrams and examined post-adoption patterns using transition matrices. The results showed that adoption was nonlinear and cyclical, with farmers frequently moving between trial, initial use, sustained use, reduced use, discontinuation, and reuse. Trial-based learning was strongly associated with sustained adoption, whereas direct adoption without prior trial was linked to higher disengagement risks. Concurrent use of multiple complementary tools further reinforced long-term commitment to site-specific nutrient management. These findings highlighted the importance of policies that expand access to PDDSTs through trial-enabled extension and distribution channels, support structured learning opportunities, and strengthen the market and institutional mechanisms needed to promote effective and sustained adoption among smallholders.